L-Dopa Pharmacokinetic Profile with Effervescent Melevodopa/Carbidopa versus Standard-Release Levodopa/Carbidopa Tablets in Parkinson’s Disease: A Randomised Study - Fabrizio Stocchi; Laura Vacca; Paola Grassini; Stephen Pawsey; Holly Whale; Stefano Marconi; Margherita Torti (Parkinson's Disease)
Objectives. To characterize the pharmacokinetic profile of levodopa (L-dopa) and carbidopa after repeated doses of the effervescent tablet of melevodopa/carbidopa (V1512; Sirio) compared with standard-release L-dopa/carbidopa in patients with fluctuating Parkinson’s disease. Few studies assessed the pharmacokinetics of carbidopa to date. Methods. This was a single-centre, randomized, double-blind, double-dummy, two-period crossover study. Patients received V1512 (melevodopa 100 mg/carbidopa 25 mg) or L-dopa 100 mg/carbidopa 25 mg, 7 doses over 24 hours (Cohort 1), 4 doses over 12 hours (Cohort 2), or 2 doses over 12 hours in combination with entacapone 200 mg (Cohort 3). Pharmacokinetic parameters included area under the plasma-concentration time curve (AUC), maximum plasma concentration (Cmax), and time to Cmax (tmax). Results. Twenty-five patients received at least one dose of study medication. L-dopa absorption tended to be quicker and pharmacokinetic parameters less variable after V1512 versus L-dopa/carbidopa, both over time and between patients. Accumulation of L-dopa in plasma was less noticeable with V1512. Carbidopa exposure and interpatient variability was lower when V1512 or L-dopa/carbidopa was given in combination with entacapone. Both treatments were well tolerated. Conclusions. V1512 provides a more reliable L-dopa pharmacokinetic profile versus standard-release L-dopa/carbidopa, with less drug accumulation and less variability. This trial is registered with ClinicalTrials.gov NCT00491998.